2018
DOI: 10.1016/j.actbio.2018.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale structural design and biomechanics of the pistol shrimp snapper claw

Abstract: The evolution success of crustaceans is largely due to the diversification of their mineralized exoskeletons and hunting appendages, which exhibit a large palette of morphometric characteristics that have adapted to meet particular functions. We explored the "snapper claw" of the pistol shrimp, which is used to generate cavitation bubbles and strike prey. Our multi-scale structure-property relationship study reveals that the snapper claw is more brittle than other fast raptorial appendages - such as the stomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…There is extensive evidence that the crustacean exoskeleton has evolved to withstand forces to which the animals are routinely subjected (Amini et al, 2018; Chen et al, 2008; Meyers et al, 2008; Taylor & Dirks, 2012). One such selective pressure is the bite force of predators.…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive evidence that the crustacean exoskeleton has evolved to withstand forces to which the animals are routinely subjected (Amini et al, 2018; Chen et al, 2008; Meyers et al, 2008; Taylor & Dirks, 2012). One such selective pressure is the bite force of predators.…”
Section: Discussionmentioning
confidence: 99%
“…is article carried out a study on the rapid closing jet mechanism of pistol shrimp's claws. e current research on the pistol shrimp mainly focuses on the following aspects: on the one hand, it focuses on the body structure and evolution process of the pistol shrimp, as well as the basic biological characteristics and living habits [13][14][15][16]; on the other hand, it focuses on the shooting of the pistol through the high-speed camera system.…”
Section: Introductionmentioning
confidence: 99%
“…The shock wave released by the collapse of cavitation bubbles is about 80 kPa at a distance of 4 cm [ 1 ], which is enough to stun and even kill the prey. When the claw is closed [ 7 ], there is an angular offset between the dactyl and the propus, which prevents physical contact between these parts, indicating that the noise is caused by the bubble collapse.…”
Section: Introductionmentioning
confidence: 99%
“…The collapsed cavitation produces high pressures and temperatures [ 4 ], thereby effectively forming a plasma with photons and shock waves through energy focusing [ 14 ]. In order to avoid the destruction of the claw structure by high-energy movement, it was found that the materials of the claw have good temperature resistance [ 15 ] and are subjected to more intense contact stresses [ 7 ].…”
Section: Introductionmentioning
confidence: 99%